Analysis of occupational health examination results among medical radiation workers in Hangzhou City - GUAN Fuqiang, ZHOU Qihong, ZHANG Tianxi, YU Huijuan (预防医学)
Objective: To investigate the occupational health status of medical radiation workers in Hangzhou City, so as to provide the basis for their occupational health risk assessment. Methods: Data on medical radiological workers who underwent occupational health examinations from 2021 to 2022 were collected through the Physical Examination Information Management System of the Hangzhou Occupational Disease Prevention and Control Hospital. The physical examination data including blood routine, eye lens, thyroid ultrasound, thyroid function, liver function, renal function and blood lipid were collected, and the abnormal rates of occupational health examinations among workers with different genders, working years and occupational exposure types were analyzed. Results: A total of 3 968 medical radiation workers were investigated, including 2 310 males (58.22%) and 1 658 females (41.78%). There were 2 039 (51.39%), 821 (20.69%) and 1 108 (27.92%) workers with 1-<6, 6-<10 years and 10 years and above of work, respectively. Diagnostic radiology was the predomenant type of exposure, with 2 240 workers accounting for 56.45%. The abnormal rates of thyroid ultrasound and blood lipid were 47.73% and 45.21%, respectively, which were relatively higher than other items. The abnormal rates of micronucleus rate, thyroid ultrasound, thyroid function and renal function were higher in females than in males, while the abnormal rates of lymphocyte count, liver function and blood lipid in males were higher in males than in females (all P<0.05). With the increase of working years, the abnormal rates of micronucleus rate and blood lipid showed upward trends (both P<0.05). There were statistically significant differences in the abnormal rates of thyroid ultrasound, liver function and blood lipid among different occupational exposure types (all P<0.05). Conclusion: Long-term low-dose ionizing radiation environment affects the thyroid, micronucleus rate and blood lipid of medical radiation workers in Hangzhou City, with differences observed among workers with different genders and occupational exposure types.